From Corrective to Collaborative: Understanding Feedback Practices of Indonesian English Lecturers - Susanti, Rini; Syahri, Indawan (Edukasi, 2025)
This study aims to investigate how Indonesian university lecturers provide feedback to students, the emotions and challenges they encounter, and the influence of culture and university regulations on feedback practices.  The study employed a narrative inquiry approach, which entails listening to participants' stories and documenting their accounts verbatim.  The research is conducted at four different universities in Indonesia, including both prominent institutions in the capital and smaller universities in lesser-known towns, to get a diverse range of data.  Four lecturers contributed to this research, each originating from diverse locations and educational backgrounds. The data was collected through individual interviews, during which the lecturers were asked several questions on their lives and experiences in providing feedback to their students. Thematic analysis was employed to examine the data. The findings indicate that feedback serves not just to rectify grammatical errors or inaccuracies in the paper but also to enhance the interpersonal relationship between lecturer and student.  The trust, caring, and culture derived from a school or nation have a significant impact.  This study demonstrates that feedback is complex, influenced by the lecturer's identity, the student's emotional state, and the institutional regulations.  The outcome provides novel insights into feedback literacy from the perspective of educators.